Extraction Of Sulfated Polysaccharide From Marine Macro Alga Gracilaria Edulis And Its Biological Applications (Applied Biological Research, 2023)
In present study, a red macroalga Gracilaria edulis, collected from  Rameshwaram Tamil Nadu (India) was used to extract sulfated polysaccharide  by using cold acidic extraction method. The yield of sulfated polysaccharide was  2.35 g from 10 g dry powdered G. edulis. The extracted sulfated polysaccharide  was analysed for antibacterial, anticancer, antioxidant and anticoagulant activities. The antibacterial activity of crude sulfated polysaccharide was  examined on three pathogenic bacteria viz., Escherichia coli, Klebsiella  pneumoniae and Staphylococcus aureus using well diffusion method. The zone of  inhibition was 20 ± 0.05 mm in case of S. aureus, followed by E. coli and K.  pneumoniae with zone of inhibitions of 15 ± 0.04 and 12 ±0.02 mm, respectively, at 50 μg mL-1sulfated polysaccharide. The anticancer activity was performed  using HeLa cancer cell line and inhibitory concentration (IC50) was 57.1 μg mL−1 as per MTT assay method. The antioxidant activity was analysed by performing  2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay and the  inhibitory concentration (IC50) value of 174.62 μg mL-1 was observed. The  anticoagulant assay was tested and partial thromboplastin time (PTT) increased  by 4.5 sec at 40 μg mL-1 of sulfated polysaccharide using activated partial thromboplastin time (APTT) assay method.
Keywords: Antibacterial activity; anticancer; antioxidant; Gracilaria edulis; sulfated polysaccharide